Mengembangkan Minat Belajar Siswa untuk Meningkatkan Pembelajaran Matematika SD Kelas Tinggi: Developing Students' Learning Interests to Improve Elementary School Mathematics Learning in High School Grades - Debby Yuliana Sinaga; Ruth Yunilisa Simangunsong; Ananda Simajuntak; Fadilany Sinaga; Yeheskiel P. Sinaga; Wahyu Hutagalung; Ucok Gunlicen Simbolon; Leni Margaretha Sitindaon; Nayla Maharani (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
Learning interest is one of the crucial aspects of education, especially in achieving learning goals. Learning interest can be interpreted as the interest or desire of students to be actively involved in the learning process. The learning interest of elementary school students is one of the critical factors that influence the success of the education process. However, in reality, many elementary school students show low learning interest. This study uses Classroom Action Research (CAR). This research was conducted at SDN 124388 Pematangsiantar in grade V students. The data needed in this study were data on students' learning interests before and after using the PjBL learning model. A research instrument was used to obtain the data in question, and it was a learning interest questionnaire. There was an increase in students' learning interest by 68.75% before and after applying the PjBL learning model in Mathematics learning for grade V students at UPTD SDN 124388 Pematangsiantar. This increase was seen in the pre-cycle stage of students with high learning interest, as many as 3 students, and 13 with low learning interest. Meanwhile, in the first cycle stage, 14 students had high learning interest, and 2 had low learning interest. Considering how vital learning interest is in achieving learning objectives, teachers are expected to carefully choose a learning model suitable for the material and the characteristics of students participating in learning.